Red dwarf. Back to Earth [videorecording (DVD)] - Naylor, Doug; Barrie, Chris, 1960-; Charles, Craig, 1964-; John-Jules, Danny; Llewellyn, Robert, 1956-; Annett, Chloë (BBC Video ; Distributed by BBC Worldwide Americas ; Distributed by Warner Home Video, 2009)
Older and none the wiser, the boys are back with the discovery that they're just characters from a TV series. Rimmer is threatened with replacement by the new, improved holograph Katrina, who is determined to guide Lister to his home planet. No one is prepared for Earth 2009, where the crew faces death in the final episode unless they can track down their creators. First, the crew attempts to track down the actors who play them in the series, and their metaphysical odyssey begins.